PENGUATAN PEMAHAMAN AKUNTANSI DAN PERANCANGAN SISTEM INFORMASI MANAJEMEN PADA UKM BATIK TULIS GIRILOYO DI DESA WISATA WUKIRSARI, IMOGIRI BANTUL - Desi Susilawati; Putri Rachmawati (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2018)
The patner of this program is Paguyuban Batik Tulis Giriloyo Wukirsari village Imogiri Bantul Yogyakarta.Paguyuban has two problems: recording the transaction manually and didnot match with acoounting standart for  SMEs (Small and Medium Enterprises). Paguyuban doesn’t have an apllication as an information management system. Information System is a tool of human in storing, processing, and organizing data. The Sophistication of information systems will accelerate the processing and management of data. Based on above, this  devotion program is  empowerment,strengthening  understanding and technical capability of accounting process  related preparing financial statement easily.and accurate. The developing information systems appication that will be used in SMEs (Small and Medium Enterprises) to obtain report of sale, report of inventory based database Access application effectively and relevance.The model of this devotion was descriptive qualitatif which measure target quantity, efficient system quality, and timeliness of preparing finanacial statement.Based on quesionare feedback from participant we got 74% of participant stated that application implementationwas easily. Effectiveness is measured by timeliness of financial reporting.The result show that financial reporting can be disclosured on time dan improve the quality of it.The results above indicate that the access database applications as information needed by  Wukirsari batik group community.to improve their performances Keywords: Effectiveness, management information system, small and medium enterprises, Empowering knowledge of accounting